MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SEKOLAH DASAR (STUDI EKSPERIMEN KUASI SISWA KELAS V SDN 164 PEKANBARU) - Randika Gustina; Gustimal Witri; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the problem of low yields of mathematics learning, so it is necessary to apply cooperative learning model pair check to help students in math increased learning outcomes. The purpose of this study was to determine whether there are differences in mathematics learning outcomes significantly between students acquire learning through cooperative learning model pair checked with conventional learning. This study is a quasi-experimental research with the study population is a fifth grade students at SDN 164 Pekanbaru while the sample is class VD as many as 30 students, consisting of 18 men and 12 women as control class and class VC as many as 36 students consisting of 12 men and 24 women as a class experiment. The results stated in pretest scores as analyzed by t meet the criteria tscore <ttable 0.15 <2.007, which means there is no significant difference and student learning outcomes in the classroom control and experiment are the same. While on the posttest scores as analyzed by t meet the criteria tscore> ttable ie 4.69> 2.007, which means that there are significant differences in posttest scores between experimental class control class. Based on the index gain, an increase in students 'mathematics learning outcomes in the experimental class has an average of 0.62 in the medium category, and the control class 0.32 with medium category, so there are differences in students' mathematics learning outcome of significant between experimental class and class control.KeyWords: Cooperative Learning Model Type Pair Check, Mathematics Learning Outcome.